2015
DOI: 10.3727/096368915x687002
|View full text |Cite
|
Sign up to set email alerts
|

Irisflorentin Modifies Properties of Mouse Bone Marrow-Derived Dendritic Cells and Reduces the Allergic Contact Hypersensitivity Responses

Abstract: Irisflorentin is an isoflavone component derived from the roots of Belamcanda chinensis (L.) DC. In traditional Chinese medicine, this herb has pharmacological properties to treat inflammatory disorders. Dendritic cells (DCs) are crucial modulators for the development of optimal T-cell immunity and maintenance of tolerance. Aberrant activation of DCs can induce harmful immune responses, and so agents that effectively improve DC properties have great clinical value. We herein investigated the effects of irisflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…While the therapeutic mechanisms of TCM remain largely undefined, it represents a treasure of medicines and deserves to be explored in depth for novel drug discovery. As a natural product that serves as an important gradient in anti-infective and anti-inflammatory TCM, IFL has been reported to suppress the secretion of LPS-induced inflammatory mediators in Raw264.7 and dendritic cells, but the underlying mechanism has not been characterized [ 16 , 17 ]. In the present study, we demonstrated that IFL could remarkably inhibit bacterial mimics, Pam3CSK4 or PGN -stimulated production of proinflammatory cytokines, such as IL-6, TNF-α, IL-12p70, IL-10 and IL-1β, not only in Raw264.7 cells but also in mouse primary macrophages (BMDMs or peritoneal macrophages) and dendritic cells through suppressing the activation of ERK and p38 MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…While the therapeutic mechanisms of TCM remain largely undefined, it represents a treasure of medicines and deserves to be explored in depth for novel drug discovery. As a natural product that serves as an important gradient in anti-infective and anti-inflammatory TCM, IFL has been reported to suppress the secretion of LPS-induced inflammatory mediators in Raw264.7 and dendritic cells, but the underlying mechanism has not been characterized [ 16 , 17 ]. In the present study, we demonstrated that IFL could remarkably inhibit bacterial mimics, Pam3CSK4 or PGN -stimulated production of proinflammatory cytokines, such as IL-6, TNF-α, IL-12p70, IL-10 and IL-1β, not only in Raw264.7 cells but also in mouse primary macrophages (BMDMs or peritoneal macrophages) and dendritic cells through suppressing the activation of ERK and p38 MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…IFT has also been shown to ameliorate 6-OHDA-induced dopaminergic neuronal degeneration and α-synuclein accumulation in Parkinson's disease models [72]. Moreover, IFT can inhibit allergic contact hypersensitivity by modifying the properties of mouse bone marrow dendritic cells [73] and can improve the LPS-induced inflammatory response of RAW 264.7 macrophages [74]. Therefore, in addition to diminishing the activity of the NLRP3 inflammasome induced by GA 50 , IFT may also have neuroprotective activities in regulating cellular anti-oxidation, anti-inflammation, and clearing amyloid in C9-ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 36 Moreover, the anti-inflammatory activity of irisflorentin may be attributed to the inhibition of NO, TNF-α, IL-1β, and IL-6 mediated by the inactivation of ERK1/2- and p38-mediated activator protein-1 pathways. 37 , 38 Lim et al 25 reported that tectorigenin exerts anti-inflammatory effects through downregulation of the inflammatory mediators iNOS, COX-2, TNF-α, and IL-6 by suppressing NF-kB/ERK/JNK-related signaling pathways. Recent experiments by Kim and co-workers (2021) showed that triterpenoids, such as isoiridogermanal and iridobelamal A, isolated from B. chinensis exert anti-inflammatory effects through the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%